Colorectal Cancer in Sudan; Clinicopathology and Surgical Outcomes from (January 2014 to January 2019) - Amin, Abdelgadir Ahmed Abdelgadir; Salim, Dr.Omer Elfaroug (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 1 (2019), 2019)
Background : Colorectal cancer is one of common cancers and second cause of death worldwide.In Sudan unfortunately there is few statistical data regarding colorectal cancer and its geographical,ethnic distribution, and pattern of presentation because of lack of statistics or under reporting. Objective: To study pattern of presentations and surgical outcome of colorectal cancer in Sudanese patients. Patients and methods : This study is descriptive cross sectional between (2014-2019); a prospective and retrospective study of histological confirmed cases of colorectal cancer was conducted at SUH. All patients who met the inclusion criteria were involved in the study. Results : We studied 124 patients in the period between (2014–2019). Highest percentage of the patients 78 (62.9%) aged between 46 – 70 years. The mean age was 67±2.4 years. Male to female ratio 1.3:1. Rectal bleeding and altered bowel habits were the most frequent presenting symptoms.Left side colonic carcinoma was 82.7% represented the majority of cases with rectal tumor accounting for 49.2% of all cases. Preoperatively, stage B was reported in majority of patients 74(59.7%) .The most common surgical managements done for the patients were low anterior resection with or without ileostomy or colostomy 32(36.8%), APR 24(19.3%), left hemicolectomy 15(12.1%), right hemicolectomy 18(14.5%), sigmoid colectomy 9(7.3 and total colectomy 4(3.2%). Final histopathology reports showed that 65% moderately differentiated adenocarcinoma 76(61.3 %). The most frequent reported postoperative complication was surgical site infection 8(6.5%) and anastigmatic leak 3(2.4). Conclusion: The mean age of patients in this study was 67±2.4 years, with male to female ratio 1.3:1. Rectal bleeding and altered bowel habits were the most frequent presenting symptoms and anemia more common in right site. The most common endoscopy findings were rectal tumor, followed by anal tumor, sigmoid colon, cecal and rectosigmoid. Anterior resection with or without ileostomy was the most frequent conducted operation. Surgical site infection was the most frequent complication followed by anastomotic leak. The final histopathology reports showed majority of cases had advanced stages “Duke's stage C and D”.